Model Perilaku Komunikasi Generasi Muda Dalam Pemanfaatan Media Digital Memasuki Era 4.0 Dan 5.0 di Kecamatan Kuranji - Zis, Sirajul Fuad; Dewi, Rahmi Surya; Efendi, Zainal (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
Changes in the communication behavior of millennial generation and generation Z in the digital era have shifted from the previous period, these changes can be seen in everyday life the lack of face-to-face interactions. Based on this, this study aims to analyze how the communication behavior of millennials and generation Z in the digital era. This study used a qualitative method with the Alfred Schutz model. The results showed four new behaviors were formed, namely the first behavior, the communication process became passive, the second behavior reduced face-to-face communication, the third behavior was unfocused communication, the fourth behavior was the dynamics of online communication.